How Will Technology Change The Face of Chinese Justice? - Chen, Benjamin Minhao; Li, Zhiyu (Columbia Journal of Asian Law, 2020)
The People’s Republic of China is embarking on an ambitious program to revolutionize its judicial institutions through information technology. Millions of cases have been published online as part of a move towards greater transparency. Courts are piloting artificial intelligence systems that promise to streamline adjudicatory processes and expand access to justice. Although other jurisdictions have employed statistical and computational methods to improve judicial decision-making, few have sought to exploit technology to the same degree. A way of understanding this exceptionalism is to view the integration of technology into law as a microcosm of China’s ambitions to emerge as a global artificial intelligence powerhouse and thereby establish itself in the first rank of nations. Seen from a different perspective, however, the technologization of the legal system responds to certain oppositions in Chinese justice. First, courts today are straining under the burden of their caseloads. The contemporary turn towards legality has swelled the number of lawsuits while the professionalization of the judicial corps also culled its ranks. Artificial intelligence enhances the speed and consistency of adjudication while online disclosure cultivates public trust in the courts. Second, adherence to legal rules and forms restored normality to a society upended by revolutionary struggle but its inflexibility also foments dissatisfaction and disrupts relationships. The ensuing governmental imperative for judges to mediate disputes has resulted in coerced settlements and delayed verdicts. Machine predictions of case outcomes, supplied by courts, guide parties to bargain in the shadow of the law, thereby preserving the voluntariness of peace and the sanctity of justice. Third, while the party-state encourages citizens to know the law and use it as their weapon, civil society and activist lawyers may rally behind a legal cause to challenge the ideological hegemony of the party-state. By helping citizens learn the law and claim their rights, databases and applications foster legal consciousness while disintermediating lawyers. Technological initiatives for administering justice simply, swiftly, and singly have thus blossomed in China because they relieve some of the tensions in its legal system. An original survey of roughly a thousand netizens and interviews of over a hundred legal aid seekers suggest that internet and artificial intelligence technologies have the potential to realize and refine a Chinese brand of authoritarian legality. But there is also a larger insight here that transcends jurisdictional boundaries and legal cultures. Obverse to the democratization of law is the marginalization of the legal profession. The advent of technology thus surfaces a tension between two dimensions of legality. The first dimension sees law as the disciplining of human conduct through rules. The second dimension, on the other hand, conceives of law as a dynamic force that, by responding to reason, has the potential to reshape the normative status quo. To the extent that lawyers are integral to the vitality of the legal order, innovations that displace them may also undermine one conception of the rule of law.